Serial estimation of urinary trypsinogen-2 levels in patients of acute pancreatitis: a new prognostic indicator - Meena, Rinki; Kumar, Surender; Sonkar, Abhinav Arun; Ahmad, Faraz; Ali, Wahid; Gaurav, Kushagra; Parihar, Anit; Singh, Vijay Kumar (International Journal of Research in Medical Sciences, 2024)
Background: Acute abdominal discomfort is a common symptom of acute pancreatitis (AP). However, because most clinics are unable to rapidly monitor pancreatic enzymes, early detection of AP is challenging. Therefore, the purpose of this study is to investigate the utility of serial urine trypsinogen-2 measurement as a prognostic indicator in individuals with AP. Methods: A total of 60 patients with AP who presented to the surgical emergency department within 72 hours of symptom onset were included in the study, regardless of sex or age. AP was classified into mild, moderate and severe according to the revised Atlanta classification. Patient’s urine samples were collected at admission, day 3, day 5, and day 7 for determination of urine trypsinogen-2 level. Results: The mean value of S. amylase (IU/l), S. lipase (IU/l), C-reactive protein (CRP) (mg/l), and urinary trypsinogen 2 were increased in severe compared with mild AP. The mean value of urinary trypsinogen 2 was significantly decreased from day 1 to day 7 after treatment in the mild, moderate, and severe AP groups. With these cut-off values, urinary trypsinogen 2 had a sensitivity of 92.3%, specificity of 42.9%, positive productive value (PPV) of 75%, and negative productive value (NPV) of 75% for diagnosing the severity of AP. These tests demonstrate the accuracy of urinary trypsinogen-2 to determine severity of AP. Conclusions: In a cross-sectional study, urinary trypsinogen-2 can be used as both diagnostic and prognostic indicator for AP.